MEFV gene testing may guide physicians for early diagnosis of familial Mediterranean fever. (5th January 2018) - Tezcan, Mehmet E.; Avci, Mehmet; Mercan, Ridvan; Aliustaoglu, Mehmet; Sargin, Mehmet
Abstract: Introduction: Familial Mediterranean fever (FMF) is characterized by recurrent attacks of polyserositis. Even though clinical assessment is accepted to be the most important factor in the diagnosis of FMF, some diagnostic procedures may help the physician. In this study, we aimed to compare the number of diagnostic procedures performed and number of physician referrals in early diagnosed and late diagnosed cases. Furthermore, we assessed which diagnostic approaches would affect the decision‐making of physicians in the early diagnosed patients. Materials and methods: We enrolled into the study 143 FMF patients who met the Tel‐Hashomer Criteria. Demographic variables, MEFV mutations (when available), diagnostic procedures (if performed) and specialist referrals were evaluated. Early diagnosis was defined as establishment of definite diagnosis within a 5‐year period after the appearance of the first symptom. Results: Early diagnosed were referred to physicians less often, and except for genetic testing, had fewer diagnostic procedures. In addition to clinical features, MEFV testing was found to be the only method that might influence the diagnosis by a physician. Conclusions: MEFV gene assessment, unlike other diagnostic procedures, might support physicians in the early diagnosis of FMF. Especially in atypical cases, MEFV gene assessment might be considered for diagnosis of FMF.